Histopathological Pattern and Post-Operative Surgical Outcomes of Gynaecological Malignancies: Three Months Experience in a Teaching Hospital of Bangladesh (Journal of Current and Advance Medical Research, 2020)
Background: Gynaecological malignancies are not uncommon in Bangladesh.Objective: The purpose of the present study was to see the histopathological pattern and post-operative surgical outcomes of gynaecological malignancies.Methodology: This clinical trial was conducted in the Department of Gynaeoncology at Dhaka, Medical College, Dhaka, Bangladesh from July to September 2019 for a period of three months. All the women presented with gynaecological malignancies with the age group of more than or equal to 18 years were selected as study population. The different patterns of gynaecological malignancies were diagnosed by histopathological examination after surgical operation. The immediate post-operative outcomes were measured.Result: A total number of 105 cases of gynaecological indoor patients were performed of which ovarian tumor was found in highest number which was 53(50.5%) cases followed by carcinoma of cervix (22.8%), endometrial carcinoma (5.7%) and vulval carcinoma (1.9%). The most common ovarian cancer was serous type carcinoma which was 14(26.4%) cases. In this study 101(96.2%) cases were survived and the rest 4(3.8%) cases were died.Conclusion: In conclusion most common cause of gynaecological operation has been performed due to ovarian tumor, carcinoma of cervix and endometrium.Journal of Current and Advance Medical Research 2020;7(2): 60-63